Political settlements and the governance of extractive industry: A comparative analysis of the longue durée in Africa and Latin America - Bebbington, A.; Abdulai, A.G.; Hinfelaar, M.; Humphreys Bebbington, D.; Sanborn, C. (My University, 2017)
This paper synthesises findings from research in Bolivia, Ghana, Peru and Zambia to address the following three questions: 1) How does the nature of political settlements affect the governance of the mining and hydrocarbon sectors and the relationships between those sectors and patterns of social inclusion and exclusion? 2) How do the circulation of ideas and the materiality of the resources in question affect this relationship? 3) What is the role of transnational ideational, institutional and political economic factors in these relationships? These questions are approached by considering the relationships between political settlements and extractive industry since the late 19th century, with special emphasis on the last three decades. The paper concludes that the nature of settlements has had important implications for the relationships between resource-dependent economies and the nature and degree of social inclusion, but far less effect on productive structure, with no political settlement having particular success in fostering economic diversification or reducing the weight of resource rents within the national economy. The paper also concludes that the very nature of the extractive economy influences the dynamics of national political settlements for the following reasons. First, the potential rents that resource extraction makes possible, and the high cost of engaging in mining or hydrocarbon industries, create incentives for particular forms of political exclusion. Second, colonial and post-colonial histories of resource extraction give political valence to ideas that have helped mobilise actors in ways that change relations of power and institutional arrangements. Third, the materiality of subsoil resources has direct implications for subnational forms of holding power that can influence resource access and control. Finally, the global nature of mineral and hydrocarbon economies, combined with the materiality of resources, bring both transnational and local political actors into the constitution of national political settlements. This makes for a particularly complex politics of scale surrounding settlements in resource-dependent economies.
Keywords: Extractive industries; political settlements; materiality; ideas; history; Bolivia; Zambia; Ghana; Peru